Effects of bulk density, filler ratio and particle geometry toward thermoplastic composite from oil palm residues / Siti Zalifah Mahmud ...[et al.] - Mahmud, Siti Zalifah; Kasim, Jamaludin; Suid, Nurul Hamiza; Mohd Sabri, Khuzaimah; Mohamad, Ahmad Shukri (2009)
Thermoplastic composites were produced from oil palm trunk sawdust and polypropylene. The filler ratio used were 10%, 20% and 30% based on dry weight of oil palm sawdust and the particle size geometry used were 425 µm, 250 µm, and 150 µm. The effect of bulk density, filler ratio and particle geometry toward physical and strength properties of thermoplastic composite were analysed. The results indicate that the smallest particle size geometry has the highest bulk density and vice versa. Higher filler ratio and particle size geometry were found to increase the physical properties of the board and the strength properties of the board decreases, respectively. In general, statistical analysis shows that the bulk density, filler ratio and particle geometry significantly influences the physical and strength properties of thermoplastic composites produced from oil palm residues.